Association of obesity profiles with type 2 diabetes in Chinese adults: Findings from the China health and nutrition survey - Zhang, Siting; Li, Weiyi; Jia, Xiaofang; Zhang, Jiguo; Jiang, Hongru; Wang, Liusen; Wang, Huijun; Zhang, Bing; Wang, Zhihong; Ding, Gangqiang (Frontiers in Nutrition, 2022)
Aims To examine longitudinal associations of profiles of obesity, continuous BMI and waist circumference (WC) with risk of type 2 diabetes in Chinese adults. Methods Data were derived from three waves(2009, 2015 and 2018) of China Health and Nutrition Survey, and 3595 adults aged 18-65 years who participated at least two waves of survey and had completed data were analyzed. Profiles of obesity were reclassified across BMI- and WC-related groups into six groups, including Group 1 with normal BMI and WC, Group 2 with normal BMI but pre-abdominal obesity, Group 3 with normal BMI but abdominal obesity, Group 4 with abnormal BMI(overweight and general obesity) and normal WC, Group 5 with abnormal BMI and pre-abdominal obesity, and Group 6 with abnormal BMI and abdominal obesity. Three-level mixed-effects logistic regressions with random intercept stratified by gender and restricted cubic splines were performed to examine ORs and 95%CIs for risk of type 2 diabetes. Results In men, compared with subjects of Group 1, those in Group 3 had higher risk, with an OR of 4.83 (95% CI: 1.99-11.74), followed by those in Group 6 (OR=4.05, 95%CI 2.32-7.08) and Group 5 (OR=2.98, 95%CI 1.51-5.87) after adjusting for all potential confounders. For women, subject of Group 6 had highest risk (OR 8.79, 95%CI 4.04-19.12), followed by Group 3(OR=3.30, 95%CI 1.23-8.86) and Group 5(OR=3.16, 95%CI 1.21-8.26). No significant association of abnormal BMI but normal WC (Group 4) was observed in both genders. Type 2 diabetes risk increased steeply at BMI of 23.5 kg/m2 and 22.5 kg/m2 or higher , and WC of 82.0 cm and 83.0 cm or higher in Chinese adult men and women, respectively (p for overall <0.001). Conclusions Regardless of the status of BMI, subjects with pre-abdominal or abdominal obesity had a higher risk of type 2 diabetes, and the risk is greater at lower BMI and WC thresholds than reflected in currently used cutoffs for assessing risk of type 2 diabetes in Chinese adults. These findings urge to inform WC modification and optimization of early screening guidelines.